(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Morozova K. A., Zelenkova N. I. Didactic model of formation of students’ information and comunication competencies in the process of studying the psychological and pedagogical disciplines. The definition of didactic model is discovered. The project of didactic model of formation of the IC-competencies of the students in psycho-pedagogical disciplines studying process is described in the article.